From Pasir Ris to Pioneer : naming practices of Singapore's Mass Rapid Transit (MRT) stations - Lim, Shaun Tyan Gin (Nanyang Technological University, 2021)
Current toponymic research in Singapore focuses on street names, or odonyms. There remains scant coverage on Singapore’s Mass Rapid Transit (MRT) station names, which are regarded as place names in their own right, and are part of the MRT system that serves millions of commuters daily. This study analyses 142 MRT station names across five MRT lines in Singapore and seeks to answer two questions: what are the languages used in naming these toponyms, and what are the naming practices that these station names exhibit? This study adopts a historical toponomastics and sociolinguistics mixed methods approach. It analyses MRT station names, using a variety of primary and secondary sources, to determine the languages and historical meanings of these toponyms. Ultimately, this work aims to be a starting point for further research on other Singaporean toponyms, particularly those in the public transport system, that might not have been fully studied.